1997
DOI: 10.1007/bf02471282
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-interferon for the treatment of idiopathic sudden sensorineural hearing loss

Abstract: We have employed alpha-interferon (IFN-alpha), an anti-viral agent, in the treatment of severe idiopathic sudden sensorineural hearing loss (ISSHL). Forty-two patients were studied and had an average hearing ability of > or = 70 dB before treatment. We also examined 2'-5' oligoadenylate synthetase (2,5A-S) activity, one of the parameters indicating anti-viral activity of IFN, to investigate the relationship between the suppression of viral proliferation and prognosis and explain the pathogenesis of ISSHL. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
8
0
4
Order By: Relevance
“…There are also some studies showing that 70-80 dB hearing loss is a cut-off level affecting the outcome of SHL therapy (20,21). Not only the severity of hearing loss, but also the configuration of the initial audiograms appears to affect the outcome (20,22). It is suggested that patients with low-frequency hearing losses -upward sloping audiograms -or mid-frequency hearing losses -flat type audiograms -may have a better prognosis (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also some studies showing that 70-80 dB hearing loss is a cut-off level affecting the outcome of SHL therapy (20,21). Not only the severity of hearing loss, but also the configuration of the initial audiograms appears to affect the outcome (20,22). It is suggested that patients with low-frequency hearing losses -upward sloping audiograms -or mid-frequency hearing losses -flat type audiograms -may have a better prognosis (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Not only the severity of hearing loss, but also the configuration of the initial audiograms appears to affect the outcome (20,22). It is suggested that patients with low-frequency hearing losses -upward sloping audiograms -or mid-frequency hearing losses -flat type audiograms -may have a better prognosis (21)(22)(23). It was also suggested that low-frequency hearing losses tend to have better recoveries as they have a better tolerance of impairment (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement rate in cases in which hearing recovered more than 30 dB -the marked recovery group by the Japanese standards -was significantly better in the defibrinogenation group [14]. In a nonrandomized control study of ·-interferon, an antiviral agent, complete recovery was found in 27 patients (64.3%) among 42 patients with the average hearing over 70 dB; this suggested the effectiveness of this drug [15].…”
Section: Efficacy Of Treatmentmentioning
confidence: 78%
“…A similar lack of improvement by antiviral therapy was found in a case suspected of having as HSV-related sudden deafness [27]. On the other hand, IFN-·, a broad-spectrum antiviral substance, which was administered to 49 sudden deafness patients showed favorable effects [44]. This study was, however, not placebo controlled and no comparison to the spontaneous cure rate could be done.…”
Section: Antiviral Treatmentmentioning
confidence: 85%